MTORC1 underlies age‐related muscle fiber damage and loss by inducing oxidative stress and catabolism. Issue 3 (29th March 2019) - Tang, Huibin; Inoki, Ken; Brooks, Susan V.; Okazawa, Hideki; Lee, Myung; Wang, Junying; Kim, Michael; Kennedy, Catherine L.; Macpherson, Peter C. D.; Ji, Xuhuai; Van Roekel, Sabrina; Fraga, Danielle A.; et al.
Abstract: Aging leads to skeletal muscle atrophy (i.e., sarcopenia), and muscle fiber loss is a critical component of this process. The mechanisms underlying these age‐related changes, however, remain unclear. We show here that mTORC1 signaling is activated in a subset of skeletal muscle fibers in aging mouse and human, colocalized with fiber damage. Activation of mTORC1 in TSC1 knockout mouse muscle fibers increases the content of morphologically abnormal mitochondria and causes progressive oxidative stress, fiber damage, and fiber loss over the lifespan. Transcriptomic profiling reveals that mTORC1's activation increases the expression of growth differentiation factors (GDF3, 5, and 15), and of genes involved in mitochondrial oxidative stress and catabolism. We show that increased GDF15 is sufficient to induce oxidative stress and catabolic changes, and that mTORC1 increases the expression of GDF15 via phosphorylation of STAT3. Inhibition of mTORC1 in aging mouse decreases the expression of GDFs and STAT3's phosphorylation in skeletal muscle, reducing oxidative stress and muscle fiber damage and loss. Thus, chronically increased mTORC1 activity contributes to age‐related muscle atrophy, and GDF signaling is a proposed mechanism.